GE_GERICHTE P/2353/2013 vom 7. Januar 2015 - GE Cour de justice (2015)
SÉQUESTRE(MESURE PROVISIONNELLE); SUPPRESSION(EN GÉNÉRAL) ; BLANCHIMENT D'ARGENT ; INFRACTION PRÉALABLE ; DROIT ÉTRANGER | CPP.197; CPP.263; CP.305bis